Design of decision support system in determining the single student tuition fee in higher education - Anwar, Muhammad; Sabrina, Elsa (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2020)
This study aims to design an application in determining the single student tuition fee using the Analytical Hierarchy Process method in Higher Education. Universitas Negeri Padang has used a system to carry out the process of grouping in Single Tuition Fee (STF), but there are still many deficiencies in determining variables. The stages in this research begin with problem analysis, needs analysis, implementation, and testing. This system architecture is based on Model-View-Controller using the Yii2 framework with the PHP programming language. This system uses the Analytical Hierarchy Process method which has a calculation of the consistency value in determining the priority level of the criteria. Determination of criteria based on a number of criteria and a number of alternatives. The results of this study provide a ranking system for each alternative. The highest-ranking is the main priority in the system in making decisions by looking at the student's economic condition.